Low sample volume origami-paper-based graphene-modified aptasensors for label-free electrochemical detection of cancer biomarker-EGFR - Wang, Yang; Sun, Shuai; Luo, Jinping; Xiong, Ying; Ming, Tao; Liu, Juntao; Ma, Yuanyuan; Yan, Shi; Yang, Yue; Yang, Zhugen; Reboud, Julien; Yin, Huabing; et al. (Nature Publishing Group, 2020)
In this work, an electrochemical paper-based aptasensor was fabricated for label-free and ultrasensitive detection of epidermal growth factor receptor (EGFR) by employing anti-EGFR aptamers as the bio-recognition element. The device used the concept of paper-folding, or origami, to serve as a valve between sample introduction and detection, so reducing sampling volumes and improving operation convenience. Amino-functionalized graphene (NH2-GO)/thionine (THI)/gold particle (AuNP) nanocomposites were used to modify the working electrode not only to generate the electrochemical signals, but also to provide an environment conducive to aptamer immobilization. Electrochemical characterization revealed that the formation of an insulating aptamer–antigen immunocomplex would hinder electron transfer from the sample medium to the working electrode, thus resulting in a lower signal. The experimental results showed that the proposed aptasensor exhibited a linear range from 0.05 to 200 ngmL−1 (R2 = 0.989) and a detection limit of 5 pgmL−1 for EGFR. The analytical reliability of the proposed paper-based aptasensor was further investigated by analyzing serum samples, showing good agreement with the gold-standard enzyme-linked immunosorbent assay
Keywords: Nanoparticles; Microfluidics; Biosensors